Operative Treatment of Cervical Myelopathy: Cervical Laminoplasty - Brett A. Braly (Advances in Orthopedics, 2012)
Cervical spondylotic myelopathy (CSM) is a degenerative process which may result in clinical signs and symptoms which require surgical intervention. Many treatment options have been proposed with various degrees of technical difficulty and technique sensitive benefits. We review laminoplasty as a motion-sparing posterior decompressive method. Current literature supports the use of laminoplasty for indicated decompression. We also decribe our surgical technique for an open-door, or “hinged”, laminoplasty.